2019
DOI: 10.1016/j.ijscr.2018.10.084
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal schwannoma: Case report and epidemiological, clinical, surgical and immunopathological analysis

Abstract: HighlightsThe schwannoma of the esophagus is a rare case report.We present a review of the main characteristics of this disease.Aspects covered epidemiological, clinical, surgical, histopathological and immunohistochemical.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 59 publications
1
15
0
3
Order By: Relevance
“…The symptomatic analysis showed that the most frequent symptoms were dysphagia (53.7%), dyspnea (10.4%), cough (4.4%), weight loss (4.4%), and chest pain (4.4%). [ 9 ] Only 1 case reported the tracheal obstruction from a benign esophageal schwannoma till now. [ 10 ] Dysphagia is the most common symptom.…”
Section: Discussionmentioning
confidence: 99%
“…The symptomatic analysis showed that the most frequent symptoms were dysphagia (53.7%), dyspnea (10.4%), cough (4.4%), weight loss (4.4%), and chest pain (4.4%). [ 9 ] Only 1 case reported the tracheal obstruction from a benign esophageal schwannoma till now. [ 10 ] Dysphagia is the most common symptom.…”
Section: Discussionmentioning
confidence: 99%
“…Oesophageal schwannomas more frequently develop in middle‐aged women and in the proximal oesophagus . Symptoms include dysphagia and weight loss.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical features and diagnostic approach: Dysphagia is, by far, the most common symptom in patients with OSs[ 21 ]. EGDS, EUS and CT scans are useful for correct clinical assessment (Figure 2B )[ 20 , 21 ]. Some OSs have been reported in association with neurofibromatosis type 2[ 20 ].…”
Section: Rare Primary Oesophageal Benign Tumours and Tumours Of Uncermentioning
confidence: 99%
“…OSs are unencapsulated but well-circumscribed tumours that are characterized by spindle cells with microtrabecular architecture. OSs can also present focal cellular pleomorphism with nuclear atypia, rare mitotic figures and a lymphoid infiltrate, also containing germinal centres[ 8 , 21 ]. Gastrointestinal schwannomas usually lack typical features present in soft tissue counterparts, such as encapsulation, nuclear palisading, vascular hyalinization and dilatation[ 8 ].…”
Section: Rare Primary Oesophageal Benign Tumours and Tumours Of Uncermentioning
confidence: 99%
See 1 more Smart Citation